2023
DOI: 10.1001/jamaophthalmol.2022.5681
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Progression of Chorioretinal Folds During Long-Duration Spaceflight

Abstract: ImportanceThe primary contributing factor for development of chorioretinal folds during spaceflight is unknown. Characterizing fold types that develop and tracking their progression may provide insight into the pathophysiology of spaceflight-associated neuro-ocular syndrome and elucidate the risk of fold progression for future exploration-class missions exceeding 12 months in duration.ObjectiveTo determine the incidence and presentation of chorioretinal folds in long-duration International Space Station crew m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 31 publications
0
17
1
Order By: Relevance
“…6 Again, this globe flattening was identified in the peripapillary region and did not extend to the macula, making it difficult to implicate presumed peripapillary forces in the development of the choroidal folds noted by Ferguson and colleagues. 1 Neither of the HDT studies nor the work here suggested that direct choroidal venous engorgement was causative. One possible explanation that may be related to observations of sequestration of cerebrospinal fluid within the optic nerve sheath being part of SANS 7 is that there is increased orbital compartment pressure from impaired venous return.…”
contrasting
confidence: 53%
See 3 more Smart Citations
“…6 Again, this globe flattening was identified in the peripapillary region and did not extend to the macula, making it difficult to implicate presumed peripapillary forces in the development of the choroidal folds noted by Ferguson and colleagues. 1 Neither of the HDT studies nor the work here suggested that direct choroidal venous engorgement was causative. One possible explanation that may be related to observations of sequestration of cerebrospinal fluid within the optic nerve sheath being part of SANS 7 is that there is increased orbital compartment pressure from impaired venous return.…”
contrasting
confidence: 53%
“…A recently published study using magnetic resonance imaging to assess globe deformation in participants exposed to HDT showed that posterior globe flattening was a frequent occurrence and could persist or even progress in the days following cessation of HDT . Again, this globe flattening was identified in the peripapillary region and did not extend to the macula, making it difficult to implicate presumed peripapillary forces in the development of the choroidal folds noted by Ferguson and colleagues . Neither of the HDT studies nor the work here suggested that direct choroidal venous engorgement was causative.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…As reported per these articles, the incidence of developing visible optic disc edema during long-duration spaceflight (LDSF) ranges from 5–29% [11 ▪▪ ,16 ▪ ,17–19,20 ▪▪ ,21–24,25 ▪ ,26,27,28 ▪ ,29,30 ▪▪ ]. In the articles that graded the visible disc edema, nearly all cases were considered Frisén grade 1 [6,7,21–23,26,29,30 ▪▪ ]. Frisén grade 1corresponds to blurring of the optic disc margin that spares the temporal quadrant [15].…”
Section: Optic Disc Edemamentioning
confidence: 99%